Separation Flow Control of a Generic Ground Vehicle Using an SDBD Plasma Actuator - Zheng Hui (Energies, 2019)
Quiescent flow and wind tunnel tests were performed to gain additional physical insights into flow control for automotive aerodynamics using surface dielectric barrier discharge plasma actuators. First, the aerodynamic characteristics of ionic wind were studied, and a maximum induced velocity of 3.3 m/s was achieved at an excitation voltage of 17 kV. Then, the optimal installation position of the actuator and the influence of the excitation voltage on flow control at different wind speeds were studied. The conclusions drawn are as follows. The effect of flow control is better when the upper electrode of the actuator is placed at the end of the top surface, increasing the likelihood of the plasma generation region approaching the natural separation location. The pressure on top of the slanted surface is primarily affected by airflow acceleration at a low excitation voltage and by the decrease of the separation zone at a high excitation voltage. The maximum drag reduction can be realized when the maximum velocity of ionic wind reaches 1.71 m/s at a wind speed of 10 m/s and 2.54 m/s at a wind speed of 15 m/s. Moreover, effective drag reduction can be achieved only by continuing to optimize the actuator to generate considerable thrust at a high wind speed.